Infant and young child feeding practice among mothers-child pair in irrigated and non-irrigated areas of Dangila district, Northwest Ethiopia, 2020: a community based comparative cross-sectional study - Mulat Tirfie Bayih; Melesse Belayneh; Wasihun Mekonen (BMC, 2024)
Abstract Background The issue of Infant and Young Child Feeding practices was widespread; it was estimated that infants were not exclusively breastfed in the first six months of life. Complementary foods were frequently provided too soon or too late, and they were often nutritionally deficient. Even, there are nutrition-sensitive activities like irrigation schemes, evidence on infant and young child feeding practices between irrigated and non-irrigated areas is scarce or limited. Objective To assess the prevalence of infant and young child feeding practices among 0-23 months of age children in irrigated and non-irrigated areas of Dangila District, North-west Ethiopia, 2020. Methods A community based comparative cross-sectional study was conducted from Dec 1, 2020, to Jun 1, 2020. A stratified sampling technique was implemented to select 823 mothers with children age 0-23 months from irrigated (411) and non-irrigated (412) kebeles. Data were collected using structured questionnaires. Multivariable logistic regression was used to identify the associated factors of infant and young child feeding practice. Adjusted odds ratios with a 95% CI were used to determine the degree of association between the independent and outcome variables. A p-value < 0.05 was used as a cutoff point to declare statistically significant variables with the outcome variable. Results Among 823 households visited, 802 respondents with a response rate of 97.8% in irrigated and 96.11% in non-irrigated areas gave complete responses. The overall prevalence of good IYCF practice was 62.5% (95% CI: 34.2, 41.3), and it shows a significant difference between irrigated (72.2%) and non-irrigated areas (52.8%). Moreover, the study identified that education primary and above (AOR = 1.889, 95% CI: 1.38, 2.648) knowledge above mean (AOR = 2.347, 95% CI: 1.555, 3.542), positive attitude (AOR = 1.716, 95% CI: 1.139, 2.587), PNC follow-up (AOR = 1.606, 95% CI: 1.154, 2.360), women's decision-making power (AOR = 1.840, 95% CI: 1.226, 2.763), and multiple delivery (AOR = 0.352, 95% CI: 0.213, 0.583) were significant factors for IYCF among 0-23 month-old children. Conclusion and recommendations The infant and young child feeding practice among 0-23 month-old children was better in an irrigated area than in a non-irrigated area. Promoting irrigation practices, empowering women, and strengthening postnatal care are recommended interventions to increase infant, young, and child feeding practices in the study area.